2004
DOI: 10.1210/en.2003-0940
|View full text |Cite
|
Sign up to set email alerts
|

Valproate Potentiates Androgen Biosynthesis in Human Ovarian Theca Cells

Abstract: In patients with epilepsy, treatment with valproate (VPA) has been reported to be associated with polycystic ovary syndrome-like symptoms including weight gain, hyperandrogenemia, and hyperinsulinemia. We examined the effect of VPA on androgen biosynthesis in ovarian theca cells isolated from follicles of normal cycling women to determine whether the hyperandrogenemia reported with VPA treatment could be a result of direct effects of VPA on the ovary. In long-term cultures of theca cells treated for 72 h with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
1
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(74 citation statements)
references
References 36 publications
3
66
1
4
Order By: Relevance
“…Western blot analysis was performed on 35 μg/ln whole-cell lysates harvested from fourth-passage normal and PCOS theca cells were grown until subconfluent and transferred into serum-free medium with and without forskolin for 24 h, as we have previously described (48). Similar results were obtained in Western analyses performed using Abcam antibody specific for the N-terminal and Sigma antibody for intrapeptide sequence of DENND1A, which were visualized using ECL (Pierce).…”
Section: Methodsmentioning
confidence: 83%
See 2 more Smart Citations
“…Western blot analysis was performed on 35 μg/ln whole-cell lysates harvested from fourth-passage normal and PCOS theca cells were grown until subconfluent and transferred into serum-free medium with and without forskolin for 24 h, as we have previously described (48). Similar results were obtained in Western analyses performed using Abcam antibody specific for the N-terminal and Sigma antibody for intrapeptide sequence of DENND1A, which were visualized using ECL (Pierce).…”
Section: Methodsmentioning
confidence: 83%
“…The theca cell preparations used in these studies have been described and characterized previously (15-17, 20, 35-38, 47). The steroidogenic phenotypes of the normal and PCOS theca cells have been reported to result from the inherent properties of the cells, rather than the cycle phase at the time that they were isolated (15,17,48). PCOS and normal ovarian tissue came from age-matched women, 38-40 y old.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, very interesting data emerged from in vitro studies. In their first study on the topic, Nelson-DeGrave and coworkers (91) demonstrated that in long-term cultures of theca cells isolated from follicles of normal cycling women and of those treated for 72 h with VPA (30-3000 micromoles), an increase in forskolin-stimulated steroidogenesis could be observed. In particular, the most pronounced effect of VPA on androgen biosynthesis was observed in the dose range of 300-3000 microns, which intriguingly represents the therapeutic levels in the treatment of epilepsy and bipolar disorder.…”
Section: Pathophysiological Aspects: From Clinical Research To Animalmentioning
confidence: 99%
“…Essa hipótese é pouco sustentável, visto que algumas pacientes com SOP e que usam valproato são magras, além do fato de que outras DAE que promovem ganho de peso não mostram relação com a SOP (39). Outra alternativa possível seria que o valproato induziria à biossíntese de androgênios ovarianos, por meio de um aumento da transcrição de genes esteroidogênicos, pelo seu estímulo à acetilação de histonas (40). Entretanto, elevações dos níveis de androgênios e alterações ovulatórias podem ser observadas em até dois terços das usuárias de valproato, mesmo sem aumento na incidência de ovários policís-ticos (41).…”
Section: Interação Das Dae Com O Eixo Gonadalunclassified